IICA Delegation in Canada : delivering results for the americas 2017 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2018)
he IICA Delegation in Canada and its partners have recognized that greater integration of the agri-food economies of the Americas is mutually beneficial. As collaborations among Canadian and Latin American and Caribbean agri-food players have increased, the IICA Delegation in Canada has become an effective broker between Canada and member countries, to find new ways to work together. In doing so, IICA Canada has become a conduit to promote shared values across the hemisphere. Its projects and activities have improved livelihoods and prospects of people across Latin America and the Caribbean as highlighted further below.